PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE LEARNING CYCLE 5E PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF SISWA KELAS VIII DI SMP NEGERI 5 KUANTAN MUDIK - Nur Atika; Sarmidin Sarmidin; Sopiatun Nahwiyah (Universitas Islam Kuantan Singingi, 2020)
The low critical thinking skills of eighth grade students at State Junior High School 5 Kuantan Mudik on in Islamic Religious Education and Character Education is marked by the result of pre-research which showed that students were less activein the learning process, students were less audacious in expressing their opinion, students were less interacting and less cooperating with friends in solving problems, students were less audacious for asking and answering the questions from theteacher, and the teacher had not yet used a varied of learning model, thus the researcher wanted to conduct Class Action Research (CAR) in order to see how the teaching and learning process that the researcher was doing run according to whatwas expected.This aim of this study was to find out how the implementation of cooperative learning model type 5E learning cycle in Islamic Religious Education and Character Education at State Junior High School 5 Kuantan Mudik and whether this learning model can improve the creative thinking skills of eighth grade students at State Junior High School 5 Kuantan Mudik. This study was class action research (CAR) which was conducted in three cycles. For collecting the data needed, this study used the data collection techniquesby observing, interviewing, and documenting.Based on this study it can be concluded that the implementation of cooperative learning model type 5E learning cycle in Islamic Religious Education and Character Education at State Junior High School 5 Kuantan Mudik was succesfull in accordance with the learning plan. It can be known from the observation of the observation sheet with the percentage of implementation reaching 81,8%. Through the implementation of the cooperative learning model 5E Cycle type in Islamic Religious Education and Character education can improve the creative thinking skills of eighth grade students at State Junior High School 5 Kuantan Mudik. This was evident from the increase in the percentage of students' creative thinking skills, in pre-action (pre cycle) only 16,34%, then in cycle 1 it increased to 34,42%, in cycle 2 it again increased to 58,61%, as well as the cycle 3 results of observations of students' creative thinking skills to 80,61%.